Type II Toxin-Antitoxin Distribution and Adaptive Aspects on Xanthomonas Genomes: Focus on Xanthomonas citri - Martins, Paula M. M.; Machado, Marcos A.; Silva, Nicholas V.; Takita, Marco A.; de Souza, Alessandra A. (Frontiers in Microbiology, 2016)
Prokaryotic toxin-antitoxin (TA) systems were first described as being designed to prevent plasmid loss in bacteria. However, with the increase in prokaryotic genome sequencing, recently many TAs have been found in bacterial chromosomes, having other biological functions, such as environmental stress response. To date, only few studies have focused on TA systems in phytopathogens, and their possible impact on the bacterial fitness. This may be especially important for pathogens like Xanthomonas spp., which live epiphytically before entering the host. In this study, we looked for TA systems in the genomes of ten Xanthomonas strains. We verified that citrus-infecting pathovars have, on average, 50% more TAs than other Xanthomonas spp. and no genome harbors classical toxins such as MqsR, RelB and HicA. Only one TA system (PIN_VapC-FitB-like/SpoVT_AbrB) was conserved among the Xanthomonas genomes, suggesting adaptive aspects concerning its broad occurrence. We also detected a trend of toxin gene loss in this genus, while the antitoxin gene was preferably maintained. This study discovers the quantitative and qualitative differences among the type II TA systems present in Xanthomonas spp., especially concerning the citrus-infecting strains. In addition, the antitoxin retention in the genomes is possibly related with the resistance mechanism of further TA infections as an anti-addiction system or might also be involved in regulation of certain specific genes.